Electrochemical corrosion of Al-Pd alloys in HCl and NaOH solutions - Palcut M.; Ďuriška L.; Špoták M.; Vrbovský M.; Gerhátová Ž.; Černičková I.; Janovec J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The corrosion performance of as-solidified Al-Pd alloys in HCl and NaOH aqueous solutions is investigated in this work. Four different alloys (Al88Pd12, Al77Pd23, Al72Pd28 and Al67Pd33, element concentrations are given in at.%) were prepared from high purity Al and Pd lumps by arc-melting in Ar. Subsequently, the alloy microstructure and phase occurrence were investigated by a combination of scanning electron microscopy and room-temperature powder X-ray diffraction. The assolidified Al-Pd alloys were found to consist of several single-phase microstructure constituents with various structures and chemical compositions, including structurally complex intermetallic phases. The polished surfaces of the Al-Pd alloys were subjected to electrochemical polarization in aqueous HCl and NaOH solutions (0.01 mol.dm-3) at 21±2°C. The corrosion experiments were conducted in a standard 3-electrode cell controlled by potentiostat. The corrosion potentials and corrosion current densities were determined by Tafel extrapolation of the experimental polarization curves. Phase dissolution has been observed on the alloy surfaces and some of the phases were preferentially corroded. The effects of the alloy microstructure and the phase occurrence are evaluated. The local nobility of individual intermetallic compounds is discussed. Finally, the conclusions for the alloys corrosion performance in acidic and basic solutions are provided.